Theoretical prediction of crystallization volume fraction for laser 3D printing of metallic glasses - QU Li-dan; HAN Bin-hui; LYU Yun-zhuo; BAI Yu-zhi (Cailiao gongcheng, 2020)
It is very important to apply an effective method to predict the crystallization degree of laser 3D printed bulk metallic glasses (BMGs) for selecting and optimizing the processing parameters of laser 3D printing. In the present study, beginning with the kinetics of crystallization of amorphous alloys, the crystallization activation energy and Arrhenius factor were obtained by testing the characteristics of the temperature of the amorphous alloy under different heating rates, then a novel method of predicting the volume fraction of crystallization for the metallic glass produced by laser 3D printing was proposed combined with the finite element simulation technology. The validity of the method was verified by using Zr50Ti5Cu27Ni10Al8(Zr50) amorphous alloy as the model system. The result shows that the volume fraction of the crystalline phase of the single-track Zr50 BMG obtained by this method is 1.23%, which is very close to the experimentally obtained crystallization phase volume fraction of 1.65%. This strongly proves the effectiveness of the theoretical prediction method for the crystallization volume fraction of laser 3D printing BMGs.